Bioorthogonally applicable multicolor fluorogenic naphthalimide–tetrazine probes with aggregation-induced emission characters. Issue 7 (13th December 2021) - Wang, Yongcheng; Teng, Yu; Yang, Hong; Li, Xiang; Yin, Dali; Tian, Yulin
Abstract : A series of naphthalimide–tetrazines were developed as bioorthogonal fluorogenic probes with multicolor emissions and aggregation-induced emission characters. Abstract : A series of naphthalimide– tetrazines were developed as bioorthogonal fluorogenic probes, which could produce significant fluorescence enhancement, notable aggregation-induced emission (AIE) characters and multicolor emissions after bioorthogonal reaction with strained dienophiles. Manipulating the π-bridge in the fluorophore skeleton allows fine-tuning of the emission wavelength and influences the AIE-active properties. With these probes, we succeeded in no-wash fluorogenic protein labeling and mitochondria-selective bioorthogonal imaging in live cells.